Ivan Cankar in krščanstvo - Bernik, France (Slavistična revija, 2006)
The author discusses Cankar's world view, paying special attention to his relationship with Christianity. The realtionship represents the essential ingredient of Cankar's world view and is displayed from his youth to the final period of his life. It is the deepest expression of the author's peronality, particularly of his exceptional ethnical sensibility. The idea of Christianity from the affirmative or negative perspective is thus organically combines with the topics of his work that have personal foundation, i.e, the image of his mother, the topic longing, and social-critical analysis of the society. The author of the article consistently takes into account the chronolgy of Cankar's view's, their dinamics, interconnectedness, and complexity, trends in the development of his often opposite and controversial views, which are eventually toned down and summed up as basic values.
Keywords: Bible; Cankar, Ivan; Christianity; ethnical sensibility; etična senzibilnost; krščanstvo; mati; mother; Slovene literature; slovenska književnost; Sveto pismo; values; vrednote